Using Student Drawings to Understand the First-Year Experience. (August 2019) - Everett, Michele C.
This article reports on an exploratory study that investigated the use of student drawings as a visual research method to understand the first-year experience. A total of 31 undeclared students enrolled in a first-year seminar participated in the study. Data generated from pre- and postdrawings of students' first semester paths were analyzed to identify emergent themes and understand experience at the group and individual levels. Findings provide novel insights about the first-year experience from the student's perspective. These new understandings have important implications that may help institutions shape and strengthen retention efforts at the student, classroom, and program levels.